The Relationship Between Listening Proficiency and Speaking Improvement In University: Consideration in Assessing Speaking and Listening - Muhammad Darrin Zuhri; Devie Reztia Anjarani; Rudi Hartono; Issy Yuliasri; Puji Astuti (International Conference on Science, Education, and Technology, 2023)
This research study aims to explore the relationship between listening proficiency and speaking improvement among university students and to identify considerations in assessing speaking and listening skills. The study employed a mixed-methods approach, including both quantitative measures and qualitative interviews, to gather comprehensive data. The findings indicate a significant positive correlation between listening proficiency and speaking improvement, suggesting that developing strong listening skills can contribute to enhanced speaking abilities. Furthermore, the study highlights several key considerations that should be taken to account when assessing speaking and listening in educational contexts. The results of this study have implications for defining the foundations of future research in English teaching methodologies and strategies, and the second language assessment process for speaking and listening skills.